3D‐Structured Stretchable Strain Sensors for Out‐of‐Plane Force Detection. Issue 26 (17th May 2018) - Liu, Zhiyuan; Qi, Dianpeng; Leow, Wan Ru; Yu, Jiancan; Xiloyannnis, Michele; Cappello, Leonardo; Liu, Yaqing; Zhu, Bowen; Jiang, Ying; Chen, Geng; Masia, Lorenzo; Liedberg, Bo; et al.
Abstract: Stretchable strain sensors, as the soft mechanical interface, provide the key mechanical information of the systems for healthcare monitoring, rehabilitation assistance, soft exoskeletal devices, and soft robotics. Stretchable strain sensors based on 2D flat film have been widely developed to monitor the in‐plane force applied within the plane where the sensor is placed. However, to comprehensively obtain the mechanical feedback, the capability to detect the out‐of‐plane force, caused by the interaction outside of the plane where the senor is located, is needed. Herein, a 3D‐structured stretchable strain sensor is reported to monitor the out‐of‐plane force by employing 3D printing in conjunction with out‐of‐plane capillary force‐assisted self‐pinning of carbon nanotubes. The 3D‐structured sensor possesses large stretchability, multistrain detection, and strain‐direction recognition by one single sensor. It is demonstrated that out‐of‐plane forces induced by the air/fluid flow are reliably monitored and intricate flow details are clearly recorded. The development opens up for the exploration of next‐generation 3D stretchable sensors for electronic skin and soft robotics. Abstract : 3D‐structured stretchable strain sensors with a stretchable sensing unit and 3D stretchable structure are reported by employing 3D printing and out‐of‐plane self‐spinning of carbon nanotubes. The sensor possesses high stretchability, multistrain detection, and strain direction recognition by one single sensor. The study paves the way for next‐generation 3D stretchable electronic sensors for electronic skin and soft robotics.